Prox1-positive cells monitor and sustain the murine intestinal epithelial cholinergic niche - Middelhoff, Moritz (Nat Commun, 2020)
The enteric neurotransmitter acetylcholine governs important intestinal epithelial secretory and immune functions through its actions on epithelial muscarinic Gq-coupled receptors such as M3R. Its role in the regulation of intestinal stem cell function and differentiation, however, has not been clarified. Here, we find that nonselective muscarinic receptor antagonism in mice as well as epithelial-specific ablation of M3R induces a selective expansion of DCLK1-positive tuft cells, suggesting a model of feedback inhibition. Cholinergic blockade reduces Lgr5-positive intestinal stem cell tracing and cell number. In contrast, Prox1-positive endocrine cells appear as primary sensors of cholinergic blockade inducing the expansion of tuft cells, which adopt an enteroendocrine phenotype and contribute to increased mucosal levels of acetylcholine. This compensatory mechanism is lost with acute irradiation injury, resulting in a paucity of tuft cells and acetylcholine production. Thus, enteroendocrine tuft cells appear essential to maintain epithelial homeostasis following modifications of the cholinergic intestinal niche.